Severe hypoglycemia and diabetic ketoacidosis in young persons with preschool onset of type 1 diabetes mellitus: An analysis of three nationwide population‐based surveys. Issue 4 (2nd March 2018) - Lindner, Lena M E; Gontscharuk, Veronika; Bächle, Christina; Castillo, Katty; Stahl‐Pehe, Anna; Tönnies, Thaddäus; Yossa, Rhuphine; Holl, Reinhard W; Rosenbauer, Joachim
Abstract : Objectives: To describe incidence rates and temporal trends of severe hypoglycemia (SH) and of hospitalizations for SH or diabetic ketoacidosis (DKA) in persons with early‐onset, long‐term type 1 diabetes (T1D) and associations of these short‐term complications with potential risk factors. Methods: This study includes data of 1, 875 persons 11.2 to 21.9 years of age with early‐onset (<5 years) and long‐term (>10 years) T1D from 3 cross‐sectional nationwide, population‐based surveys conducted in 2009/2010, 2012/2013 and 2015/2016 using standardized questionnaires. Negative binomial regression was used to estimate incidence rates per 100 person‐years (py), temporal trends and associations between potential risk factors and outcomes. Results: The crude incidence rate of SH showed a decreasing trend over time ( P for trend = .004), disappearing after adjustment for confounders ( P for trend = .341). In contrast, adjusted rates of SH‐ and DKA‐associated hospitalizations did not change significantly between 2009 and 2016 ( P for trend = .306 and .774, respectively). Associations between sex, diabetes duration, insulin treatment regimen, hypoglycemia awareness as well as physical activity and SH were found, while family structure was associated with hospitalizations for SH. Family structure, socioeconomic status (SES), diabetes duration, and hemoglobin A1c values showed associations with DKA‐related hospitalizations. Conclusions: After adjustment, rates of SH and SH‐ or DKA‐associated hospitalization showed no significant changes in recent years. Structured education programs focusing on high‐risk groups as, for example, persons with T1D living with 1 biological parent and the parents' partner or those with a low SES, should be implemented to reduce incidence rates of hospitalizations.